2019
DOI: 10.3390/app9245568
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study on the Critical Frequency Response of Jet Engine Rotors for Blade-Off Conditions against Bird Strike

Abstract: Vibrations are usually induced in aero engines under their normal operating conditions. Therefore, it is necessary to predict the critical frequencies of the rotating components carefully. Blade deformation of a jet engine under its normal operating conditions due to fatigue or bird strike is a realistic possibility. This puts the deformed blade as one of the major safety concerns in commercially operating civil aviation. A bird strike introduces unbalanced forces and non-linearities into the engine rotor syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the early simulations based on finite element analysis, the bird impact load was modelled as a uniform pressure vs. time at the impact area [10]. Afterwards, bird models based on Lagrangian, Eulerian, Arbitrary Lagrangian-Eulerian (ALE), and Smoothed Particles Hydrodynamics (SPH) formulations were developed and used in the bird strike simulations [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In the early simulations based on finite element analysis, the bird impact load was modelled as a uniform pressure vs. time at the impact area [10]. Afterwards, bird models based on Lagrangian, Eulerian, Arbitrary Lagrangian-Eulerian (ALE), and Smoothed Particles Hydrodynamics (SPH) formulations were developed and used in the bird strike simulations [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…(2) the translational rotational modes (i.e., cylindrical rotational modes) are typical for the symmetric mechanical structures; and (3) the presence of torsional critical speeds and torsional vibration modes indicates the adequacy of the selected geometrical and material properties of the modeled structure [16,[18][19][20][21][22][23][24][25]. The output results of the rotational dynamic analysis in ANSYS Mechanical are provided as numerically computed values of eigenvalues f (Hz) (i.e., natural frequencies, also referred to as whirl frequencies) as a function of the rotational speed Ω (rpm) of the modeled rotating structure (i.e., f (Ω)).…”
Section: Numerical Modelingmentioning
confidence: 99%
“…(1) a strong dependency of the Coriolis effect, which affects the stiffness of the system, is reflected in the split (i.e., bifurcation) of the vibrational rotational modes; (2) the translational rotational modes (i.e., cylindrical rotational modes) are typical for the symmetric mechanical structures; and (3) the presence of torsional critical speeds and torsional vibration modes indicates the adequacy of the selected geometrical and material properties of the modeled structure [16,[18][19][20][21][22][23][24][25].…”
Section: Numerical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Liebich [30] designed and developed a test rig that represented the rotor dynamic behavior of an aeroengine almost in a full size scale, which could study the unbalance response of the whole engine model. Badshah et al [31] established the rotor parts including the fan, compressor, and turbine, carried out the analysis of bird impact fan based on the SPH method, and obtained the impact response of the fan. Then, the modal analysis of the rotor parts with bird impact deformation was carried out at different rotational speeds, and it was found that the change of rotational speed had a greater impact on the modal response of the damaged engine rotor.…”
Section: Introductionmentioning
confidence: 99%